IMPLEMENTASI PEMBELAJARAN BERBASIS JURNALISTIK MELALUI TEMA "JURNALIS CILIK: BERITA DI SEKITARKU" PADA SISWA KELAS V SEKOLAH DASAR MUHAMMADIYAH KRONGGAHAN - Azhar Nur Firdaus; Azamul Fadhly Noor Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Indonesian language learning in elementary schools needs to be carried out in an innovative way so that students' literacy skills develop through learning experiences that are relevant to everyday life and have meaning. However, the process of learning to write news texts is still dominated by the provision of theoretical material, so students do not have sufficient opportunities to observe, collect information, and compile news based on facts. This study aims to explain how to implement journalism-based learning with the theme "Little Journalists: News Around Me" to fifth-grade students at Muhammadiyah Kronggahan Elementary School. This study uses a qualitative approach and descriptive research type. The research subjects included one fifth-grade teacher and 28 students. Data were collected through observation, interviews, and document recording, then analyzed using the Miles and Huberman interactive analysis model consisting of three stages: reducing data, presenting data, and drawing conclusions. The study shows that journalism-based learning is successfully implemented through three stages: planning, implementation, and evaluation in an organized manner. Observation, interviewing, writing news, and presentation activities can improve students' participation, teamwork, communication, and literacy skills in creating news based on facts in the school environment. Thus, learning using a journalistic approach through the theme "Little Journalist: News Around Me" can be a more contextual, more active, and more focused choice for learning Indonesian in elementary school